Vibration based condition monitoring and fault diagnosis of wind turbine planetary gearbox: A review. (1st July 2019) - Wang, Tianyang; Han, Qinkai; Chu, Fulei; Feng, Zhipeng
Highlights: Review vibration based fault diagnosis methods of wind turbine planetary gearbox. Fundamental analysis of the planetary gearbox vibration response are reviewed. Fault enhancement and operation pattern effect elimination are reviewed. Feature extraction and fault diagnostics strategy are reviewed. Prospects of vibration based fault diagnosis methods are discussed. Abstract: As one of the most immensely growing renewable energies, the wind power industry also experiences a high failure rate and operation & maintenance cost. Therefore, the condition monitoring and fault diagnosis of a wind turbine (WT) generator set are highly needed. Among different components of a WT generator set, WT planetary gearbox plays a crucial role in transmission and leads to relatively higher failure rate and longer downtime. Towards this, a number of studies have been reported in both the academic journals and conference proceedings. This paper provides a systemic and pertinent state-of-art review on WT planetary gearbox condition monitoring techniques on the topics of fundamental analysis, signal processing, feature extraction, and fault detection. Moreover, a few valuable open issues are pointed out and potential research directions are suggested.